Zigbee-based data acquisition system for online monitoring of grid-connected photovoltaic system - Shariff, F.; Abd Rahim, N.; Ping, H.W. (Elsevier, 2015)
For grid-connected photovoltaic (PV) system, monitoring is considered as a crucial aspect for observing the stability and performance of the system. The simplest method is to have the data collected and transmitted across data cables. Due to the cost and technical limitations of the data cable, the monitoring station needs to be located reasonably close to the monitored plant. Apart being inconvenient, the use of data cable often adds capital and maintenance cost to the system. In this research project, a Zigbee-based wireless monitoring system is developed for online monitoring of a grid-connected photovoltaic system. Parameters like temperature, irradiation, PV power output and grid inverter power output are monitored. The implementation process, including design and development of the hardware and software, is explained in detail. A user-friendly web-application is also developed, such that the monitored data is easily accessible via internet. To validate the performance, the system has been implemented on 1.25 kW(p) grid-connected photovoltaic system. (C) 2014 Elsevier Ltd. All rights reserved.